Inclusiveness in mental health research: a survey of attitudes, awareness, and actions among journal editors - Patrizia Pezzoli; Weili Zhai; Joan Marsh; Essi Viding (European Science Editing)
Background: Improving inclusiveness in mental health research merits attention as we seek to reduce inequalities in mental health. Academic journals can promote inclusiveness through editorial practices related to the selection of content and the composition of journal editorial boards. Objectives: To investigate the attitudes, awareness, and actions of journal editors concerning inclusiveness in mental health research and editorial practices. Methods: We surveyed 74 chief and senior editors, representing 55 prominent journals in neuroscience, psychiatry, and psychology (2021 impact factor M = 8.04, SD = 10.76). Results: Most respondents (74–99%) acknowledged the importance of inclusiveness in mental health research, and a majority (62–78%) were familiar with existing guidelines. Half or fewer of the journals (49–50%) had policies for selecting content that is diverse, and 20% had policies regarding inclusion of individuals with lived experience of mental health challenges. Well over half the journals (57–72%) had policies to widen diversity among their editorial boards and roughly half (43–53%) among peer reviewers, although only a few (18–23%) included among their editors or peer reviewers individuals with lived experience of dealing with mental health challenges. Conclusions: This study highlighted an intention-action gap, with positive attitudes and awareness but limited editorial practices promoting inclusiveness in mental health research. Inclusion of individuals with lived experience emerged as an area in particular need of improvement. We discuss potential strategies that journals might consider to foster inclusiveness, such as diversity training, publication checklists, and infrastructure that supports participatory approaches.